2024
DOI: 10.3390/foods13020194
|View full text |Cite
|
Sign up to set email alerts
|

Whole Flour of Purple Maize as a Functional Ingredient of Gluten-Free Bread: Effect of In Vitro Digestion on Starch and Bioaccessibility of Bioactive Compounds

Luisina Monsierra,
Pablo Sebastián Mansilla,
Gabriela Teresa Pérez

Abstract: The growing demand for gluten-free products requires the study of alternatives to produce nutritionally and technologically favorable foods. The aim was to evaluate the content and antioxidant capacity of gluten-free bread enriched with whole flour of purple maize (PM) and how starch and bioaccessibility of antioxidant compounds were modified during in vitro digestion. Gluten-free bread was prepared with the addition of 34%, 50%, and 70% PM, and white maize bread served as control. The content of total polyphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…These findings suggest that "Moragro" maize has the potential to be a valuable crop for both human health and sustainable agriculture. 6 Purple maize is a rich source of phenolic compounds, mainly anthocyanins, that give a dark purple-red color to the grains. The anthocyanin composition of some purple maize has been well studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that "Moragro" maize has the potential to be a valuable crop for both human health and sustainable agriculture. 6 Purple maize is a rich source of phenolic compounds, mainly anthocyanins, that give a dark purple-red color to the grains. The anthocyanin composition of some purple maize has been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…The flour also has a higher content of slowly digestible and resistant starch in comparison to traditional white maize flour. These findings suggest that “Moragro” maize has the potential to be a valuable crop for both human health and sustainable agriculture …”
Section: Introductionmentioning
confidence: 99%
“…RS type I, RS type II, RS type III, and RS type IV) are used in the baking of bread [7,9]. However, it was found that the sensory and textural properties of bread are negatively affected by increasing the RS content, such as through crumb stiffening and darker colors [10]. Also, some research has found that several RSs at certain levels do not significantly affect the sensory quality of bread [9].…”
Section: Introductionmentioning
confidence: 99%